Islamic Economic Governance: A Yemen and United States Comparative Study for Indonesia's Sustainable Development - Roikhatul Jannah; Naufal Luthfi Alifa (IQTISHODUNA, 2026)
Islamic economics is fundamentally rooted in the concept of maqasid al-shariah, which represents the ultimate objectives of Islamic law in promoting human welfare (maslahah) and preventing harm (mafsadah). Rather than merely regulating transactional legality, maqasid sharia provides an ethical framework guiding economic systems toward social justice, sustainability, and equitable wealth distribution. Classical scholars such as Al-Ghazali and Al-Shatibi identified five core dimensions: protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal). In economic practice, hifz al-mal emphasizes lawful circulation of wealth, the prohibition of exploitative practices such as riba and gharar, and redistributive instruments such as zakat and waqf. Meanwhile, hifz al-nafs is reflected in poverty alleviation and financial inclusion, underscoring Islamic finance's social orientation. The experience of Yemen demonstrates the potential of maqasid-based empowerment through Islamic microfinance and community-oriented banking, though weak regulation and political instability limit its effectiveness. In contrast, Islamic financial institutions in the United States adapt maqasid principles within a secular framework through ethical financing models, despite regulatory and literacy challenges. For Indonesia, maqasid sharia offers a strategic foundation for sustainable development by integrating Islamic social finance, fintech innovation, and inclusive economic policies. Ultimately, the success of Islamic economics should be assessed by its ability to promote justice, resilience, and collective prosperity rather than profit alone.